Effect of HPMC and ethyl cellulose polymeric granules and its combinations in press coated tablets of lornoxicam: fabrication and in vitro characterization - Dineshmohan, S.; Gupta, V R M; Ramesh, A.; Harika, V.; Sravani, T. (International Current Pharmaceutical Journal, 2015)
The main objective of the present exploration was to formulate and evaluate chronomodulated press-coated tablets to deliver the NSAID lornoxicam, when a pain in the joints, functional disability persist in the early morning time is typically observed in most Rheumatoid arthritis (RA) patients. Pre formulation studies and drug excipient compatibility studies were carried out for lornoxicam and excipients. Core tablets containing lornoxicam was prepared by direct compression method and the tablets were subjected to various pre-compression and post-compression parameters (C1-C4 formula) based on the above result best core tablet batch was selected and used for press coating processes. HPMC and EC granules were used as controlled release polymers in the outer layer. These tablets were subjected to pre and post compression parameters, finally the tablets were evaluated for lag time and in vitro dissolution. Results of preformulation studies were acceptable limits. No interaction was observed between lornoxicam and excipients by FTIR. The results of pre and post compression studies were within limits. Formulation code CC3 was identified as best formulation that extends a release profile with 6 h lag time followed by complete lornoxicam release after 8 h. From the graphical representation it can be well perceive that this is perfectly fit in to Korsemeyer which had a Regression coefficient (R2) of 0.9431. The results of the in-vitro release data of this layer were fitted to the Korsemeyer-Peppas equation to examine the release pattern of the drug from the polymeric system. The drug release was identified as super case II transport as the n value found to be more than 0.89. Dineshmohan et al., International Current Pharmaceutical Journal, September 2015, 4(10): 447-452